PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII-B SMP IT AL-FITYAH PEKANBARU - Fatma Nauli Butar-Butar; Syofni Syofni; Nahor Murani Hutapea (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is classroom action research that aims to improve learning process and to improve mathematics learning outcomes of students with applied the model of Problem Based Learning. The subject of research is student of class VIII-B SMP IT Al-Fityah Pekanbaru in the second semester academic years 2017/2018, which amounted to 28 female students. The research consisit of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. At the end of every cycle the quiz will be implemented. The instruments of data collection were observation sheets and test of mathematics learning outcomes. The observation sheets were analyzed in narrative descriptive, while test of mathematics learning outcomes were analyzed in statistics descriptive. Narrative descriptive analysis shows that there has been improvement of learning process from before action to cycle I and from cycle I to cycle II. Learners participate actively in learning process and increasingly independent in solving mathematical problems given. Statistics descriptive analysis shows that students mathematics learning outcomes improve and there has been an improve in the number of students who reach the KKM. The number of students who reached the KKM from the base value to the quiz I improved by 25% and from quiz I to quiz II improved by 21.43%. Results of research indicates that implementation model of Problem Based Learning can improve learning process and improve mathematics outcomes from the students class VIII-B SMP IT Al-Fityah in the second semester academic years 2017/2018.Key Words: Mathematics Learning Outcomes, Problem Based Learning, Classroom Action Research